2003
DOI: 10.1007/s00592-003-0044-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of physical activities of various intensities on the energy expenditure of type 2 diabetic men

Abstract: Interventions that focus on changing lifestyles through the combined use of dietary management, weight reduction, and increased physical activity are essential for managing type 2 diabetes mellitus (T2DM). The objective of the present study was to examine mildly obese T2DM patients [ n=10; mean age (+/-SD), 51.29+/-6.80 years; body mass index (BMI), 30.26+/-6.19 kg/m(2); and glycosylated haemoglobin (HbA(1c)), 8.16+/-1.16%)] and to compare them with normoglycaemic persons ( n=10; age, 53.00+/-9.48 years; BMI, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Huang et al (28) reported that BMR in these patients was 8.4% higher in females and 4.6% higher in males than in the corresponding nondiabetic subjects. Maiolo et al (29) also reported that BMR was 35% higher in diabetic patients. It is important to note that BMR was not adjusted for body composition in these studies which may explain a large portion of the increase in BMR.…”
Section: Discussionmentioning
confidence: 89%
“…Huang et al (28) reported that BMR in these patients was 8.4% higher in females and 4.6% higher in males than in the corresponding nondiabetic subjects. Maiolo et al (29) also reported that BMR was 35% higher in diabetic patients. It is important to note that BMR was not adjusted for body composition in these studies which may explain a large portion of the increase in BMR.…”
Section: Discussionmentioning
confidence: 89%
“…At speeds of walking range from 0.6 to 1.6 m/s, Petrovic et al (66) presented a general pattern of a higher cost of walking (express as milliliters per kilogram per minute) in diabetic patients with neuropathy (significant difference at all speed of walking) and in diabetic patients without neuropathy (significant difference at 1.4 and 1.6 m/s) in comparison with healthy subjects. However, Maiolo et al (71) found no significant difference in net EE of walking (at three different intensities) between patients with DM and healthy people.…”
Section: Energy Expenditure In Subjects With Dmmentioning
confidence: 96%